COMPUTER CRIME - Abdulakhatov Islombek (Academia Science Repository, 2023)
Computer crime is a growing concern involving the unauthorized use of computer technologies to commit illegal activities. This article explores various forms of computer crime, including hacking, identity theft, fraud, and cyber terrorism. It emphasizes the need to differentiate between computer crimes and computer security breaches, as well as the importance of understanding and preventing these crimes. The article also discusses the prevalence of online fraud schemes, the dangers of pedophiles using the internet, and the risks associated with social media. It concludes by highlighting the need for individuals to take proactive measures to protect their personal information and online activities. [1]